Faktor-faktor yang Mempengaruhi Kelelahan pada Anak dengan Penyakit Jantung Bawaan: Systematic Review - Imamah Indah Cahyani; Nur Agustini; Fajar Tri Waluyanti (Universitas Faletehan, 2026)
Fatigue is a multidimensional symptom commonly experienced by children with congenital heart disease (CHD) and contributes to reduce quality of life. This study aimed to identify factors influencing fatigue in children aged 2 to 18 years with CHD. A systematic review was conducted by searching eight databases: PubMed, ScienceDirect, Scopus, SAGE Journals, Wiley, Taylor and Francis, OpenAlex, and EBSCOhost. Seven observational articles to analyzed, sample sizes ranging from 30 to 931 children. The result indicated that fatigue was associated with frailty status, reduced health-related quality of life, decreased exercise capacity, greater disease severity, suboptimal family functioning, and a higher number of medical procedures. These findings highlight the importance of a comprehensive nursing approach that integrates clinical assessment and family-centered interventions to support fatigue management and improve overall well-being in children with CHD.